Asia-Pacific Security : Policy Challenges - Lovell, David W., 1956- (Book collections on Project MUSE., 2003)
Since September 11, 2001, our newspapers have been filled with the 'war on terror'; our governments have mobilized their resources for 'homeland security'; and people everywhere are braced for more terrorist attacks. Yet while the new threat is genuine, we must not lose sight of the continuing security concerns in the Asia-Pacific. Tensions persist on the Korean peninsula, in the Taiwan Straits and the South China Sea, and in Kashmir. The region is well supplied with weapons of mass destru ...